Effect of Natalizumab Treatment on Circulating Plasmacytoid Dendritic Cells: A Cross-Sectional Observational Study in Patients with Multiple Sclerosis - Kivisäkk, Pia; Francois, Katiana; Mbianda, Julvet; Gandhi, Roopali; Weiner, Howard L.; Khoury, Samia J. (PloS one, 2014)
Dendritic cells (DCs) serve a critical role both in promoting and inhibiting adaptive immunity. The goal of this study was to investigate the effect of natalizumab (NTZ) treatment on DC numbers, phenotype, and function in patients with multiple sclerosis (MS). Frequency and phenotype of myeloid and plasmacytoid DCs (MDCs and PDCs, respectively) were analyzed in blood from two separate cohorts of untreated, interferon-treated, or NTZ-treated MS patients. In addition, PDCs were stimulated with CpG-containing oligonucleotides or co-cultured with homologous T cells in the presence or absence of NTZ in vitro to determine functional effects of NTZ treatment. We observed that NTZ treatment was associated with a 25-50% reduction in PDC frequency in peripheral blood as compared to untreated MS patients, while the frequency of MDCs was unchanged. PDCs in NTZ-treated patients displayed a mature, activated phenotype with increased expression of HLA-DR, TLR9, CCR7, IL-6 and IL-12. In contrast, in vitro treatment with NTZ did not increase markers of PDC activation or their ability to induce T cell differentiation. Our study shows that NTZ treatment is associated with a reduced frequency of PDCs in the peripheral circulation, but that PDCs in NTZ-treated individuals display an activated phenotype. Taken together the data suggests that transmigration of activated PDCs is preferentially affected by blockade of integrin α4 leading to an increased frequency of activated PDCs in blood.